Does wild food contribute to food security? Evidence from rural Bhutan - Panharoth Chhay; Dil Bahadur Rahut; Sonam Tashi; Jordan Chamberlin (Asian Development Bank Institute (ADBI), 2023)
We use primary data to examine the potential role of wild foods in alleviating food insecurity among rural farmers in Bhutan during the COVID-19 pandemic. We find that food-insecure households are more likely to collect wild foods, suggesting that food-insecure households are consuming wild foods as a coping mechanism. Therefore, it is crucial to include wild food considerations in regional, national, and international food security policy to promote resilience and reduce vulnerability in rural communities. Food security policies may enable the use and consumption of wild foods as a complementary source of food and nutrition, especially in remote areas. Further, the government should implement policies on managing wild foods as it is a public good, and its conservation is crucial for preserving biodiversity.
Keywords: Q18; Q20; 330; wild foods; food insecurity; rural farmers; Bhutan